A method for forming a heterogeneous metal-based copper binary alloy capping layer and a semiconductor interconnect structure
Patent Information
- Application Number
- CN202611004712.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-07
- Publication Date
- 2026-10-27
AI Technical Summary
然而,单一异质金属直接沉积在多晶铜表面时,极易在铜的大角度晶界处发生异质金属原子的势驱动扩散,使异质金属层无法在铜表面实现均匀致密沉积,导致不连续、不均匀的表面异质金属钝化层特征,易在键合界面处引入额外的键合缺陷;同时,化学机械研磨腐蚀后的铜大马士革表面本身具有一定粗糙度,异质金属薄膜的直接沉积易在沉积界面处产生微缺陷,进一步加剧直接沉积异质金属钝化层带来的界面可靠性问题
1.PVD铜纳米晶粒对异质金属原子带来晶界扩散限制影响,避免其发生不均匀扩散,使异质金属主要限制在修饰层内并保持均匀连续分布;
Smart Images

Figure CN122995674A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of semiconductor manufacturing technology, specifically relating to a method for forming a heterogeneous metal-based copper binary alloy modification layer and a semiconductor interconnect structure. Background Technology
[0002] Hybrid bonding technology, capable of achieving submicron interconnect pitch, ultra-low power consumption, and high integration density, has become a key technology for 3D integration. However, the copper surface in hybrid bonding is prone to oxidation, forming a nanoscale natural oxide layer that hinders the diffusion of copper atoms at the interface. This necessitates high-temperature annealing at 350°C to 400°C or higher for several hours for traditional copper-copper direct bonding, leading to wafer warpage, thermal stress, and electrical problems in front-end devices. If the bonding temperature is lowered, microvoids easily form at the interface, resulting in insufficient bonding reliability.
[0003] Currently, the common practice in this field is to directly deposit pure inert metals such as Au (gold), Ag (silver), and Ru (ruthenium) as passivation layers after chemical mechanical polishing (CMP) of Damascus copper, using physical vapor deposition (PVD) or electroless plating, to suppress copper surface oxidation. According to the literature [Commun. Eng. 2025, 4, 216], a 3 nm Ag passivation layer achieves an interfacial bonding strength of approximately 1050 N under low-temperature annealing at 180 °C for 2 h, which is twice the strength compared to direct copper-copper bonding. However, when a single heterometal is directly deposited on the surface of polycrystalline copper, potential-driven diffusion of heterometal atoms is very likely to occur at the large-angle grain boundaries of copper. This makes it impossible for the heterometal layer to achieve uniform and dense deposition on the copper surface, resulting in discontinuous and uneven surface heterometal passivation layer characteristics. This can easily introduce additional bonding defects at the bonding interface. At the same time, the copper damascus surface after chemical mechanical polishing has a certain roughness. Direct deposition of heterometallic films can easily generate micro-defects at the deposition interface, further aggravating the interface reliability problems caused by direct deposition of heterometallic passivation layers.
[0004] Therefore, how to obtain a uniform and dense anti-oxidation heterometallic interface and achieve highly reliable copper-copper interface bonding in the manufacturing strategy of passivation layer modification is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0005] In existing technologies, to prevent oxidation of copper surfaces, it is common practice to directly deposit pure inert metals such as Au, Ag, and Ru as passivation layers on Damascus copper surfaces. However, due to the inertia and established mindset of this technology, researchers have long overlooked the potential of the "heterometallic-copper binary alloying" approach in suppressing grain boundary migration and improving interface uniformity.
[0006] This invention proposes a method for forming a heterogeneous metal-based copper binary alloy modification layer for hybrid bonding, comprising the following steps: a) A substrate is provided, on the surface of which a damascus copper embedded in a dielectric layer is formed, wherein a surface profile with a controllable groove depth D is formed on the surface of the damascus copper. b) A patterned photoresist mask layer is formed on the surface of the dielectric layer, the photoresist mask layer covering the surface area of the dielectric layer and exposing the surface of the damascus copper; c) A binary alloy modification layer is deposited on the structure obtained in step b) by physical vapor deposition, such that the binary alloy modification layer is deposited on the exposed damascus copper surface and the surface of the photoresist mask layer. d) Use an organic solvent to strip the structure obtained in step c) to remove the photoresist mask layer and the modification layer material above it, so that the binary alloy modification layer is selectively retained only on the damascus copper surface; e) Perform pre-bonding thermal annealing on the structure obtained in step d).
[0007] The binary alloy modification layer is composed of a heterometallic metal and a copper metal, wherein the heterometallic metal is selected from Ag, Au, Pd or Ru, and the copper atom content in the binary alloy modification layer is less than 50% and greater than or equal to 10%.
[0008] Pre-bonding heat annealing can promote interfacial diffusion and bonding between the binary alloy modification layer and the underlying damascus copper, making the modification layer more continuous and dense. At the same time, it can bridge the interfacial defects generated during the deposition process, thereby improving the reliability and yield of subsequent copper-copper bonding.
[0009] According to a specific embodiment of the present invention, the damascus copper is formed by etching trenches and / or vias in the dielectric layer, then filling them with copper and performing chemical mechanical polishing to give the damascus copper surface a surface profile with controllable groove depth.
[0010] For example, the photoresist is either a positive photoresist or a negative photoresist.
[0011] According to a specific embodiment of the present invention, the patterned photoresist mask layer is formed by spin coating, exposure, and development processes.
[0012] As an example, the structure of the Damascus copper is a single inlay structure or a double Damascus structure.
[0013] According to a specific embodiment of the present invention, the physical vapor deposition method is multi-palladium magnetron co-sputtering.
[0014] Preferably, the pre-bonding thermal annealing treatment is performed at a temperature of 100~200℃ for 1 hour. Too low a temperature results in weak activation, while too high a temperature affects the reliability of the front-end devices.
[0015] Preferably, before the pre-bonding heat annealing treatment, the surface of the structure obtained in step d) is mechanically planarized to form a groove between the binary alloy modification layer and the surrounding dielectric layer, the groove having a depth of 1-5 nm.
[0016] According to a specific embodiment of the present invention, the dielectric layer includes a first dielectric layer and a second dielectric layer; the first dielectric layer is deposited on the surface of the substrate, and the second dielectric layer is located between the two first dielectric layers; the first dielectric layer is silicon oxide or silicon carbide, and the second dielectric layer is silicon nitride.
[0017] Preferably, the allowable range of the groove depth D is d ~ (5+d) nm, where d is the thickness of the binary alloy modification layer.
[0018] Preferably, the thickness of the binary alloy modification layer is 2~10 nm. 2 nm ensures that the modification layer can continuously and uniformly cover the copper surface, effectively preventing oxidation. When the thickness is thinner, the modification layer may be discontinuous and the process requirements are higher. 10 nm and below is more economical and easier to control. If the modification layer is too thick, it will affect the interdiffusion effect of the bonding interface, and a thicker modification layer will affect its own interface uniformity.
[0019] According to a specific embodiment of the present invention, the substrate is a silicon substrate.
[0020] According to a specific embodiment of the present invention, a barrier layer / adhesive layer is provided between the damascus copper dielectric layers to prevent copper from diffusing into the dielectric layers and to improve the interfacial bonding strength.
[0021] The present invention also provides a semiconductor interconnect structure for hybrid bonding, comprising: a substrate, a dielectric layer formed on the surface of the substrate, and damascus copper embedded in the dielectric layer; and a binary alloy modification layer; wherein the binary alloy modification layer selectively covers only the surface of the damascus copper, and the binary alloy modification layer is prepared by the method described above.
[0022] This invention breaks through the aforementioned conventional thinking and proposes to construct a heterogeneous metal-based copper binary alloy modification layer on the surface of Damascus copper. Utilizing the grain boundary diffusion confinement effect in the alloy, it cleverly solves the problems of interface inhomogeneity and discontinuity faced by single heterogeneous metal passivation layers. The alloy consists of copper and one metal selected from Ag (silver), Au (gold), Pd (palladium), and Ru (ruthenium). (The selected heterogeneous metal has excellent inertness to prevent oxidation, and the copper atom content is less than 50%; simultaneously, copper atoms and the selected heterogeneous metal have high mobility to promote the interdiffusion effect at the subsequent bonding interface, as shown in Table 1; among them, Ag and Au have relatively excellent conductivity; Pd and Ru have good high-temperature stability and strong resistance to electromigration). By leveraging the grain boundary diffusion restriction effect between the heterometallic metal and copper in the binary alloy modification layer, the excessive diffusion and segregation of heterometallic metal atoms to the grain boundaries of the copper damascus structure are mitigated, resulting in a continuous and uniform modification layer. This improves the interface defects encountered when a single heterometallic metal is directly deposited as a passivation layer. Simultaneously, under pre-bonding thermal annealing, the copper component serves as a sacrificial buffer to achieve interface healing between the heterometallic layer and the copper damascus surface structure, eliminating deposition interface defects and achieving a high-quality modification layer deposition effect. Due to the curvature-driven growth effect of PVD nanocrystal copper, high-quality interface bonding is simultaneously promoted on the two bonded modification layers.
[0023] Table 1 Multi-target magnetron co-sputtering was employed to simultaneously deposit copper and a heterometallic material at low temperatures (<80℃) to form a heterometallic copper binary alloy modification layer. The copper after physical vapor deposition exhibits a high grain boundary density nanocrystalline copper structure (grain size approximately 100 nanometers). This heterometallic material and nanocrystalline copper structure primarily exhibit a grain boundary diffusion confinement effect within the modification layer region, resulting in uniform diffusion mainly within the modification layer rather than segregation along large-angle grain boundaries on the copper damascus surface.
[0024] Pre-bonding thermal annealing provides thermal activation energy (100~200℃, 1 hour) to drive atomic diffusion within the alloy modification layer: the heterogeneous metal atoms, which constitute the majority, serve as the matrix, forming a passivation layer enriched with heterogeneous metal atoms, effectively blocking the oxidation of the damascus copper surface by oxygen; at the same time, some copper nanocrystals in the modification layer undergo grain growth due to the curvature-driven effect, and through grain boundary migration, they fill the interface voids that may occur at the interface of the underlying damascus copper grains, forming a good deposition interface state.
[0025] The atomic composition ratio of Cu alloy metals can be controlled by sputtering process. x -Metal (1-x)(x < 50%), which can effectively limit the diffusion behavior of heterogeneous metals within the modified layer in subsequent processes, and simultaneously form a good modified layer deposition interface and a continuous, dense passivation modified layer. Through the above synergistic mechanism, a good low-temperature bonding effect is ultimately achieved.
[0026] Compared with the existing technology of directly depositing a single heterogeneous metal passivation layer, this invention constructs a heterogeneous metal-based copper binary alloy modification layer. By utilizing the synergistic effect of grain boundary diffusion restriction and curvature-driven grain growth under different atomic composition ratios, it achieves the surface enrichment passivation effect of inert metal and the optimization of the interface quality of the copper self-buffered layer on the Damascus copper surface, as well as the promotion of interfusion at the bonding interface, without increasing the complexity of the process. This provides a new approach for high-quality low-temperature bonding methods based on modification layers.
[0027] This scheme proposes to construct a heterogeneous metal-based copper binary alloy modification layer on the surface of Damascus copper. Through the grain boundary diffusion restriction effect, the segregation of heterogeneous metal atoms to the large-angle grain boundaries of copper Damascus is suppressed, forming a continuous and uniform modification layer. Under pre-bonding thermal annealing, the heterogeneous metal is enriched to form a dense passivation layer to block oxidation. At the same time, the curvature-driven growth of copper nanocrystals fills the interface voids caused by the surface morphology of Damascus copper and insufficient diffusion of metal atoms during PVD.
[0028] Technical effect 1. PVD copper nanocrystals restrict the diffusion of heterogeneous metal atoms at grain boundaries, preventing uneven diffusion and confining the heterogeneous metal mainly within the modification layer, maintaining a uniform and continuous distribution. 2. The copper component in the alloy can serve as a sacrificial buffer layer, actively mitigating interface defects generated on the damascus copper surface during the deposition of the modified layer under the drive of pre-bonding thermal annealing; at the same time, the curvature-driven growth effect of the copper nanocrystals promotes the inter-fusion of copper interfaces during bonding.
[0029] 3. The binary alloy modification layer of the present invention has an anti-oxidation function, which can prevent the oxidation of the Damascus copper surface during the pre-bonding process and avoid the problem of limited diffusion of copper atoms in the later stage. Therefore, it is not necessary to perform pre-bonding and post-annealing bonding in a vacuum or inert atmosphere. Attached Figure Description
[0030] Figure 1 This is a cross-sectional schematic diagram of the interconnect structure formed by the copper damascus process provided in step a) of Embodiment 1 of the present invention.
[0031] Figure 2 This is a schematic diagram of the structure after the patterned photoresist mask layer is formed in step b) of Embodiment 1 of the present invention.
[0032] Figure 3This is a schematic diagram of the structure after depositing the binary alloy modification layer in step c) of Embodiment 1 of the present invention.
[0033] Figure 4 This is a schematic diagram of the structure after step d) of removing the photoresist and mechanically planarizing in Embodiment 1 of the present invention.
[0034] Figure 5 This is a schematic diagram of the structure obtained by pre-bonding and hot annealing the binary alloy modification layer in the two steps d) of Embodiment 1 of the present invention.
[0035] In the figure: 100-substrate, 101-dielectric layer, 1011-first dielectric layer, 1012-second dielectric layer, 102-damascus copper, 103-barrier layer / adhesive layer, 104-photoresist mask layer, 105-binary alloy modification layer. Detailed Implementation
[0036] To enable those skilled in the art to better understand the technical solutions in this application, the present invention will be further described below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only some embodiments of this application, and not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of this application.
[0037] This invention provides a semiconductor interconnect structure, comprising the following steps: Step a): Forming the Damascus copper structure like Figure 1 As shown, a substrate 100 is provided, and damascus copper 102 embedded in a dielectric layer 101 is formed on the surface of the substrate 100 by a damascus process. The surface of the damascus copper 102 is formed with a surface profile having a controllable groove depth (Dishing) D.
[0038] In one specific embodiment of the present invention, the copper damascus interconnect process is first completed, followed by chemical mechanical polishing to obtain a damascus copper surface profile with a controllable groove depth (Dishing) D.
[0039] In one specific embodiment of the present invention, the substrate 100 is a silicon substrate.
[0040] In a specific embodiment of the present invention, the dielectric layer 101 includes a first dielectric layer 1011 and a second dielectric layer 1012. The first dielectric layer 1011 is deposited on the substrate 100. The first dielectric layer 1011 is silicon oxide or silicon carbide and serves as the main dielectric to form the interconnect network framework. The second dielectric layer 1012 is silicon nitride and is located between the two first dielectric layers 1011. It serves as a buffer layer in the damascus etching process to achieve a damascus copper structure with a consistent aspect ratio.
[0041] In a specific embodiment of the present invention, a barrier layer / adhesive layer 103 is provided between the dielectric layer 101 and the damascus copper 102 to prevent copper from diffusing into the dielectric layer and to improve the interfacial bonding strength.
[0042] According to a specific embodiment of the present invention, the damascus copper 102 fills the trenches and / or vias formed by etching the dielectric layer 101.
[0043] In a specific embodiment of the present invention, since a binary alloy modification layer needs to be physically vapor-deposited on the surface of Damascus copper 102, the allowable range of the groove depth (D) on the copper surface can be correspondingly widened. Assuming the thickness of the binary alloy modification layer deposited on the copper surface is d nm, its upper limit for groove depth can be expanded to (5+d) nm. This design effectively reduces the precision requirements of the chemical mechanical polishing process and improves the process window. That is, the allowable range of groove depth D is d ~ (5+d) nm. Furthermore, the design of the groove depth D can also minimize excessive protrusions during the passivation layer deposition process.
[0044] Step b): Fabrication of the photoresist mask layer like Figure 2 As shown, a patterned photoresist mask layer 104 is formed on the surface of the dielectric layer 101. The photoresist mask layer 104 covers the surface areas of the dielectric layer 101 and the barrier / adhesive layer 103, and exposes the surface of the damascus copper 102.
[0045] In a specific embodiment of the present invention, the photoresist mask layer 104 is formed by spin coating, exposure, and development processes. Specifically, in Figure 1 Positive photoresist is spin-coated onto the surfaces of the structure, namely the damask copper 102, the barrier / adhesive layer 103, and the dielectric layer 101. The substrate with the spin-coated photoresist is then soft-baked, and the photoresist is exposed through a mask. After exposure, development is performed to obtain a patterned photoresist mask layer 104. The photoresist mask layer 104 covers the surface areas of the dielectric layer 101 and the barrier / adhesive layer 103, and exposes the surface of the damask copper 102.
[0046] In another specific embodiment of the present invention, the photoresist is a negative photoresist.
[0047] Step c): Deposit a binary alloy modification layer like Figure 3 As shown, a binary alloy modification layer 105 is deposited on the structure obtained in step b) by physical vapor deposition, such that the binary alloy modification layer 105 is deposited on the exposed damascus copper 102 surface and the photoresist mask layer 104 surface. Step d): Peeling The structure obtained in step c) is immersed in an organic solvent for stripping, completely removing the photoresist mask layer 104 along with the binary alloy modification layer 105 deposited above it, leaving only the binary alloy modification layer 105 on the surface of the damascus copper 102. Then, the binary alloy modification layer 105 is mechanically planarized to form a groove relative to the surrounding dielectric layer 101, with a groove depth of 1-5 nm, resulting in the structure shown below. Figure 4 The structure shown.
[0048] Step e): Pre-bonding thermal annealing The structure obtained in step d) is subjected to pre-bonding thermal annealing.
[0049] According to a specific embodiment of the present invention, the binary alloy modification layer 105 obtained in the two steps d) is first fully bonded together, and then pre-bonding heat annealing is performed in an air atmosphere to obtain the structure shown in the figure. Figure 5 The structure is shown. The pre-bonding thermal annealing treatment is performed at a temperature of 100~200℃ for 1 hour.
[0050] Compared with the existing technology of directly depositing a single heterogeneous metal passivation layer, the present invention constructs a copper binary alloy modification layer and utilizes the synergistic mechanism of grain boundary diffusion restriction effect and curvature-driven grain growth to achieve a highly uniform and reliable modification layer deposition interface without increasing process complexity, thereby promoting low-temperature and high-quality bonding.
[0051] According to a specific embodiment of the present invention, a multi-target magnetron co-sputtering process is used to simultaneously deposit a heterogeneous metal and copper under low-temperature deposition conditions (<80°C). By controlling the ratio of the deposition rates of the targets and the deposition time, binary alloy modification layers 105 with different atomic compositions are obtained, and the atomic fraction of copper in the binary alloy is controlled within the range of 10% to 50%. The heterogeneous metal is selected from inert metals Ag, Au, Pd, or Ru. After deposition, the photoresist mask layer 104 is stripped using an organic solvent to obtain the binary alloy modification layer 105 deposited only on the surface of Damascus copper 102. The heterogeneous metal atoms and nanocrystalline copper atoms diffuse into each other to form a uniformly distributed heterogeneous metal passivation layer. Due to the presence of the inert metal, the modification layer has an anti-oxidation function. Correspondingly, the higher the atomic fraction of the inert metal atoms, the better the anti-oxidation effect of the modification layer.
[0052] According to a specific embodiment of the present invention, during the pre-bonding thermal annealing process at 100~200℃ for 1h, the thermal field provides sufficient thermal activation energy, and depending on the different proportions of nanocrystalline copper in the binary alloy modification layer, different degrees of interfacial diffusion effect are generated on the damascus copper surface.
[0053] When the copper atomic fraction is 10%, a significant small-doping effect is formed with a heterogeneous polycrystalline metal as the matrix and nanocrystalline copper as the guest. Under pre-bonding thermal annealing, copper, as a small component of the heterogeneous metal matrix, diffuses to the deposition interface, inducing rapid growth of Damascus copper grains on the Damascus copper surface with a high concentration of copper atoms. This actively bridges the defects at the Damascus copper deposition interface, forming annealed twins with lower energy. This diffusion, in turn, restricts the migration of heterogeneous metal atoms to the copper Damascus deposition interface, forcing them to accumulate on the surface of the modification layer to form a uniform and continuous heterogeneous metal passivation layer, achieving an anti-oxidation effect. When the copper mass fraction is high, approaching 50%, copper can no longer be considered a small component. The composition ratio with heterogeneous metal atoms makes it difficult for copper to gradient and agglomerate into copper layers and heterogeneous metal layers. After annealing, the crystalline copper structure and the heterogeneous metal structure are mixed. Due to the presence of an inert heterogeneous metal layer, the modification layer can still provide a certain degree of anti-oxidation. During bonding, the increased copper nanocrystals exhibit grain growth-driven creep, promoting interfacial solubility and achieving good bonding results. However, when the copper content is high (e.g., >50%), more copper nanocrystals are oxidized, which affects bonding quality. Therefore, the mass fraction of copper in heterometallic copper binary alloys should be less than 50%.
Claims
1. A method for forming a heterogeneous metal-based copper binary alloy modification layer, characterized in that, Includes the following steps: a) A substrate is provided, on the surface of which a damascus copper embedded in a dielectric layer is formed, wherein a surface profile with a controllable groove depth D is formed on the surface of the damascus copper. b) A patterned photoresist mask layer is formed on the surface of the dielectric layer, the photoresist mask layer covering the surface area of the dielectric layer and exposing the surface of the damascus copper; c) A binary alloy modification layer is deposited on the structure obtained in step b) by physical vapor deposition, such that the binary alloy modification layer is deposited on the exposed damascus copper surface and the surface of the photoresist mask layer. d) Use an organic solvent to strip the structure obtained in step c) to remove the photoresist mask layer and the modification layer material above it, so that the binary alloy modification layer is selectively retained only on the damascus copper surface; e) Perform pre-bonding thermal annealing on the structure obtained in step d); The binary alloy modification layer is composed of a heterometallic metal and a copper metal, wherein the heterometallic metal is selected from Ag, Au, Pd or Ru, and the copper atom content in the binary alloy modification layer is less than 50% and greater than or equal to 10%.
2. The method according to claim 1, characterized in that, The damascus copper is formed by etching trenches and / or vias in the dielectric layer, then filling them with copper and performing chemical mechanical polishing to give the damascus copper surface a surface profile with a controllable groove depth.
3. The method according to claim 1, characterized in that, Before the pre-bonding heat annealing treatment, the surface of the structure obtained in step d) is mechanically planarized to form a groove between the binary alloy modification layer and the surrounding dielectric layer, the groove having a depth of 1-5 nm.
4. The method according to claim 1, characterized in that, The physical vapor deposition method is multi-palladium magnetron co-sputtering.
5. The method according to claim 1, characterized in that, The pre-bonding heat annealing treatment is performed at a temperature of 100~200℃ for 1 hour.
6. The method according to claim 1, characterized in that, The dielectric layer includes a first dielectric layer and a second dielectric layer; the first dielectric layer is deposited on the surface of the substrate, and the second dielectric layer is located between the two first dielectric layers; the first dielectric layer is silicon oxide or silicon carbide, and the second dielectric layer is silicon nitride.
7. The method according to claim 1, characterized in that, The allowable range of the groove depth D is d ~ (5+d) nm, where d is the thickness of the binary alloy modification layer.
8. The method according to claim 1, characterized in that, The thickness of the binary alloy modification layer is 2~10nm.
9. The method according to claim 1, characterized in that, The substrate is a silicon substrate, and a barrier layer / adhesive layer is disposed between the damascus copper dielectric layers to prevent copper from diffusing into the dielectric layers and to improve the interfacial bonding strength.
10. A semiconductor interconnect structure, characterized in that, include: A substrate, a dielectric layer formed on the surface of the substrate, and damascus copper embedded in the dielectric layer; And a binary alloy modification layer; The binary alloy modification layer is selectively applied to the surface of the damascus copper only, and the binary alloy modification layer is prepared by the method described in any one of claims 1 to 9.